Mexiletine or catheter ablation after amiodarone failure in the VANISH trial. (1st February 2018) - Deyell, Marc W.; Steinberg, Christian; Doucette, Steve; Parkash, Ratika; Nault, Isabelle; Gray, Chris; Essebag, Vidal; Gardner, Martin; Sterns, Laurence D.; Healey, Jeff S.; Hruczkowski, Tomasz; Rivard, Lena; et al.
Abstract: Introduction: In patients with ischemic heart disease and ventricular tachycardia (VT) refractory to high dose amiodarone, the two most common therapeutic options are adjunctive mexiletine therapy or catheter ablation. There are little existing data on the efficacy of these strategies. We examined the relative efficacy of adjunctive mexiletine and catheter ablation among patients enrolled in the VANISH trial. Methods: All subjects enrolled in the VANISH trial who had VT refractory to high dose (≥ 300 mg daily) amiodarone at baseline were included. Per protocol, subjects randomized to escalated drug therapy received adjunctive mexiletine. Results: Nineteen of the 259 patients were receiving high‐dose amiodarone at baseline and 11 were randomized to escalated therapy with mexiletine and 8 to ablation. The adjunctive mexiletine group had a higher rate of the primary composite outcome (death, VT storm, or appropriate shock) in comparison to catheter ablation (HR 6.87 [2.08–22.8]). Over 90% of the patients in the adjunctive mexiletine/group experienced a primary endpoint during a median 9.2 months' follow‐up. There was no difference in the rate of adverse events between the two groups. Conclusions: Mexiletine has limited efficacy in the treatment of recurrent VT despite high‐dose amiodarone therapy, in patients with ischemic heart disease. Catheter ablation is a superior strategy in this population.